The Common Approach to Article 1: The Scope of Each State's Obligation to Ensure Respect for the Geneva Conventions. (24th March 2020) - Robson, Verity
Abstract: Common Article 1 of the Geneva Conventions of 1949 is foundational, but not exceptional: the duty to respect and ensure respect for the Conventions must be considered within the framework of public international law as a whole. The Article obliges each High Contracting Party and its organs to respect the Geneva Conventions, and to ensure respect for these Conventions by the population over which it exercises authority and any other persons or groups whose conduct is attributable to it. This scope is demonstrated by the ordinary meaning of the term, subsequent agreements, subsequent practice and other relevant rules of international law, and confirmed by reference to the travaux preparatoires . In particular, erga omnes status does not affect it. As a matter of good faith performance of the Conventions, each High Contracting Party also has a duty not to encourage violations by others. Common Article 1 does not require, as some authors have argued, the prevention or termination of breaches of the Geneva Conventions by other parties to conflict, but High Contracting Parties may choose to take steps toward doing so, as a matter of policy.